Public debt and economic growth: Does governance quality matter? - Septina, Penny; Adrison, Vid (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2025)
Rising public debt has become a central policy concern as governments increasingly rely on borrowing to finance development and recovery programs. Yet the impact of debt on growth remains debated, depending on how effectively countries manage and allocate borrowed resources. This study examines the relationship between public debt and economic growth, with governance quality as a moderating factor. Anchored in an extended neoclassical framework, public debt is treated as a financing tool whose effect depends on governance quality and fiscal allocation. Using panel data from 188 countries for 1996–2023, the analysis applies fixed-effects and instrumental-variable estimations based on non-overlapping five- and ten-year averages to capture medium- also long-term dynamics while addressing endogeneity. The results show that debt reduces growth when governance is excluded; however, the effect becomes positive and significant once governance interactions are included—especially in the five-year model with lagged debt as an instrument. By contrast, the three-way interaction among debt, governance, and public capital is insignificant in the medium term, suggesting that investment effects may require longer horizons or stronger institutional alignment. Overall, the findings highlight that sound governance and efficient fiscal allocation are prerequisites for transforming public debt from a fiscal burden into a driver of sustainable economic growth.